A revision of the genus Macrolygistopterus Pic, 1929 (Coleoptera, Lycidae, Calochromini) - Ferreira, Vinicius S. (Zootaxa, 2016)
A taxonomic review of the Lycid genus Macrolygistopterus Pic, 1929 with illustrations of diagnostic characters, geographic distribution maps and an identification key to the species is presented. Also, a key to the world Calochromini is given. Of the 12 species of the genus, 9 were studied: M. succinctus (Latreille, 1811), M. quadricostatus (Buquet, 1842), M. caeruleus (Gorham, 1884), M. germaini Pic, 1930, M. grandjeani Pic, 1930, M. subparallelus Pic, 1930, M. testaceirostris Pic, 1930, M. simoni Pic, 1930 and M. kirschi Pic, 1931 were redescribed and their status as valid species is confirmed. The lectotypes and paralectotypes were designated for all those examined species. M. bilineatus (Pic, 1923), M. diversicornis Pic, 1930 and M. bipartitus Pic, 1933 remain as valid species since these specimens were not available for this study. M. succinctus var. scutelaris Pic, 1930 is proposed here as new junior synonym of M. succinctus (Latreille, 1811).